USE OF FOREIGN EXPERIENCES IN MANAGEMENT OF TOURIST ENTERPRISESH - Ismoilov Ravshanjon Baxriddinovich; Xurramov Zufarjon; Badiyev Baxtinur; Olimjonov Islomjon (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
Today, tourism is one of the main factors of global economic growth, which not only provides many competitive jobs, but is also a source of growth for some developing countries. Tourism has a multiplier effect that directly or indirectly affects the development of more than fifty sectors of the world economy. Modern Russian tour operators are actively introducing new technologies to increase their competitiveness in the global tourism market. Thus, digitalization of tourism significantly changes the business processes in the sector and allows to maximize profits by reducing the cost of production, therefore, it is crucial for the competitiveness of the sector in the long term.